The Compressed Work Week as Organizational Change: Behavioral and Attitudinal Outcomes - Ronen, Simcha; Primps, Sophia B. (Academy of Management Review, 1981)
The results from recent studies on the compressed work week have been compiled and categorized in order to provide some basis for generalizing the effects of the work schedule on employee attitudes and behavior. It appears that attitudes toward the compressed week are favorable, with some generalization to job attitudes. Performance outcomes are ambiguous, although there are no reported decreases; fatigue seems to be the only negative aspect of the longer day. An examination of mediating variables suggests more complex relationships between the implementation of the compressed work week and potential outcomes. These relationships are described and directions are indicated for future research.